COUNSELING AND TRAINING OF INTERVENTION MODEL LOCAL PLANTS TO OVERCOME STUNTING (TALAS) FOR HEALTH WORKERS AT MONTASIK HEALTH CENTER, ACEH BESAR - Tahara Dilla Santi; Aditya Candra; Radhiah Zakaria (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2024)
The counseling and training activities carried out at the Montasik Health Center aim to increase insight and knowledge about the use of herbal plants in an effort to reduce stunting cases in the Montasik Health Center work area which can improve public health. Community service activities carried out by lecturers and students are a "community partnership empowerment" program granted by the Ministry of Research, Technology and Higher Education. Stunting cases in the Montasik Health Center work area are very high (261 stunting, 144 wasting, and 348 underweight children). Based on this, an intervention model is needed that can be applied by officers at the Montasik Health Center to mothers who have toddlers in preventing new stunting cases and increasing insight to increase the use of Moringa leaves as a source of high nutrition as a food additive for toddlers and children. The intervention model provided includes five food menus that are liked by toddlers and children, namely moringa meatballs, moringa ice cream, moringa nuggets, moringa noodles, moringa cookies. The results of this community service are expected to contribute to Montasik Health Center officers to implement a food menu intervention model with the addition of Moringa leaf flour to meet the nutritional needs of toddlers and children so that in the long term it can reduce stunting cases.